2018
DOI: 10.18186/thermal.465692
|View full text |Cite
|
Sign up to set email alerts
|

Numerical Study of Milk Fouling Thickness in the Channel of Plate Heat Exchanger

Abstract: Fouling phenomenon remains at the forefront of problems that concern manufacturers using heat exchangers. Despite the large number of studies carried out, the mechanism and the evolution of this phenomenon remain poorly understood. In the dairy industry, fouling is a very important parameter seen as it can affect the quality of food product. Studies carried out on this phenomenon during milk heat treatment have led to the conclusion that lacotglobulin protein is the main precursor of fouling. Indeed, the therm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
1
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 11 publications
0
1
0
Order By: Relevance
“…In the dairy industry, fouling is a very important parameter seen as it can affect the quality of food products. Studies on this phenomenon showed during milk heat treatment have led to the conclusion that protein is the main precursor of fouling (Aouanouk et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…In the dairy industry, fouling is a very important parameter seen as it can affect the quality of food products. Studies on this phenomenon showed during milk heat treatment have led to the conclusion that protein is the main precursor of fouling (Aouanouk et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…In contrast to the above studies, for the systems working in the two-phase flow, the presence of the nanoparticles can apply a thermal resistance which suppresses the heat transfer mechanisms on the surface. Apart from this issue, there are extensive studies in which it has been shown that HTC can be augmented due to the NPs [7,9,[33][34][35][36][37][38][39]. Hence, more investigations are still required to understand the mechanism of boiling in two-phase systems.…”
Section: Introductionmentioning
confidence: 99%